Correlation between dietary patterns and cognitive function in older Chinese adults: A representative cross-sectional study - Gou, Ruoyu; Qin, Jian; Pang, Weiyi; Cai, Jiansheng; Luo, Tingyu; He, Kailian; Xiao, Song; Tang, Xu; Zhang, Zhiyong; Li, You (Frontiers in Nutrition, 2023)
Abstract Objective: To investigate the relationship between dietary patterns and cognitive function in an older adults (≥ 60 years old). Methods: Food intake was quantitatively assessed by the Food Frequency Questionnaire (FFQ), and cognitive function was assessed by the Chinese version of the Simple Mental State Examination Scale (MMSE). Four major dietary patterns were identified by FA (Factor Analysis Method). The relationship between dietary Patterns and cognitive function was evaluated by logistic regression. Results: A total of 884 participants were included in the study. Four dietary patterns (Vegetable & Mushroom, Oil & Salt, Seafood & Alcohol, and Oil tea dietary patterns) were extracted. In the total population, Model Ⅲ results showed that the fourth quartile of dietary pattern factor scores for Vegetable & Mushroom was (0.399, 7.056). The Vegetable & Mushroom dietary pattern may be a protective factor for cognitive function, with P-value=0.033, OR (95%CI):0.578 (0.348, 0.951) in Model Ⅲ (Adjusted for covariates: Sex, Ethnic, Marital, Agricultural activities, Smoking, Drinking, Hypertension, Diabetes, Dyslipidemia, BMI, Dietary fiber). In the ethnic stratification analysis, the scores of dietary pattern factors of Vegetable & Mushroom among the Yao participants were (0.333,5.064). Vegetable & Mushroom diet pattern may be a protective factor for cognitive function, P-value=0.012, OR (95%CI): 0.415(0.206,0.815). Conclusion: The fourth quartile of the Vegetable & Mushroom dietary pattern scores showed dose-dependence and a strong correlation with cognitive function. Currently, increasing vegetable & mushroom intake may be one of the effective ways to prevent and mitigate cognitive decline. It is recommended to increase dietary intake of vegetables and mushroom foods.